IoT-based inventory monitoring system for SMEs - Lora Ristio Gultom; Vina Sari Yosephine (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2024)
Industry 4.0's pervasive digital ideas have completely changed how businesses operate. A lot of big businesses have switched to digital systems. However, due to a lack of funding and digital infrastructure, SME sector digitalization issues still exist. Inventory management is one of the many manual methods that many SMEs still have to rely on, which makes it prone to error. To manage inventories more accurately and effectively, manual systems must be changed. The goal of this project is to improve inventory management efficiency by creating a dependable and affordable automated system. A cloud database is connected to the system to provide quick inventory monitoring on warehouse shelves. Prototyping and statistical testing are used in the study technique to evaluate the system's dependability. Using an Internet of Things-based single-board computer, the research creates an inventory monitoring system. With a daily implementation cost of IDR 642.92, the system is deemed cost-effective based on inventory monitoring results on warehouse shelves. Because the system's performance reached a Cronbach's alpha value greater than 0.8, the inventory management system used in the study is regarded as dependable for application in real-world systems to increase inventory management accuracy